To Take Risk is to Face Loss: A Tonic Pupillometry Study - Yechiam, Eldad; Telpaz, Ariel (Frontiers in Psychology, 2011)
The construct of risk taking is studied through the prism of the relation between tonic arousal and risk taking behavior. Several theories have proposed that high aroused individuals tend to exhibit risk aversion. We posit that this arousal-behavior association is activated much more strongly in risks with losses, as losses increase arousal and trigger relevant traits associated with the sensitivity to risk. In three studies we examined risk taking in experience-based decision tasks, with either token losses or relative losses (in the gain domain). In Study 1 we found a negative correlation between pre-task pupil diameter and risk taking in the loss domain but not in the gain domain. In study 2 we re-analyzed a previous pupillometry dataset involving symmetric mixed gains and losses. We found that the negative correlation in this mixed condition emerged even while the participants did not show loss aversion. This finding was replicated in Study 3. Thus, the effect of losses on arousal provides sufficient conditions for the moderation of the tonic arousal-behavior association. The findings suggest an important role for losses in the psychological and physiological experience of risk.